The search for an autoimmune origin of psychotic disorders: prevalence of autoantibodies against hippocampus antigens, glutamic acid decarboxylase and nuclear antigens - Hoffmann, Carolin Correia (2021)
The etiology of psychotic disorders is still unknown, but in a subgroup of patients symptoms might be caused by an autoimmune reaction. In this study, we tested patterns of autoimmune reactivity against potentially novel hippocampal antigens. Serum of a cohort of 621 individuals with psychotic disorders and 257 controls were first tested for reactivity on neuropil of rat brain sections. Brain reactive sera (67 diseased, 27 healthy) were further tested for antibody binding to glutamic acid decarboxylase (GAD) isotype 65 and 67 by cell-based assay (CBA). A sub-cohort of 199 individuals with psychotic disorders and 152 controls was tested for the prevalence of anti-nuclear antibodies (ANA) on HEp2-substrate as well as for reactivity to double-stranded DNA, ribosomal P (RPP), and cardiolipin (CL). Incubation of rat brain with serum resulted in unidentified hippocampal binding patterns in both diseased and control groups. Upon screening with GAD CBA, one of these patterns was identified as GAD65 in one individual with schizophrenia and also in one healthy individual. Two diseased and two healthy individuals had low antibody levels targeting GAD67 by CBA. Antibody reactivity on HEp-2-substrate was increased in patients with schizoaffective disorder, but only in 3 patients did antibody testing hint at a possible diagnosis of systemic lupus erythematosus. Although reactivity of serum to intracellular antigens might be increased in patients with psychotic disorder, no specific targets could be identified. GAD antibodies are very rare and do not seem increased in serum of patients with psychotic disorders.